Simulation of the performance of a hybrid ground-coupled heat pump system on the basis of wet bulb temperature control. (5th September 2016) - Han, Zongwei; Ju, Xiaomei; Ma, Xiao; Zhang, Yanhong; Lin, Min
Highlights: A wet bulb temperature control strategy for heat pump system is proposed. A method of determining the control parameters is introduced. Performance of the new strategy and two common strategies is compared. Abstract: Considering the characteristics of a cold source of air and soil, an operation control strategy of a hybrid ground-coupled heat pump system (HGCHPS) was proposed based on wet bulb temperature control. A method of determining the control parameters was introduced, and a mathematical model of the main components of the system was developed. Dynamic simulation of the system performance was studied under this operation strategy and two additional commonly used control strategies. The results showed that the system had good heating and air conditioning safeguards under the control of the wet bulb temperature. The annual average coefficients of performance ( COP s) of the cooling and heating system were 3.93 and 4.09, respectively. The annual average COP of heating and air conditioning was 3.96. The long-running performance of this operation strategy was better than those of the two additional control strategies and was able to maintain the soil's thermal balance around soil heat exchangers (SHEs) with an annual cycle.